Penerapan Buku Ajar Nahwu Metode Ihfadz Di Madrasah Diniyyah Al Amiriyyah Darussalam Blokagung Banyuwangi - Rosyid Ridho; Munirul Abidin (Institut Agama Islam Darusssalam Blokagung, 2023)
ABSTRACT Research related to learning nahwu science using the ihfadz method at madrasah diniyyah al amiriyyah Darussalam Blok Agung Banyuwangi aims to provide a stimulus to students so that it is easy and fast to understand the yellow book by previous scholars. This research is also used to eliminate the perspective of the general public who think that reading and understanding the yellow book is difficult. The research method used by researchers is in the form of a qualitative descriptive method, namely research conducted to describe and analyze phenomena, events, social activities, attitudes and thoughts of people either in groups or individually. The data analysis technique used is the method of observation, interviews and documentation. The results of this study are the implementation of the nahwu curriculum using the ihfadz method, which among its applications is memorizing and understanding texts and their understanding which will then be practiced in application books according to the level of each volume. In learning there are also factors that support this learning and factors that even hinder the learning of this curriculum.